2020
DOI: 10.1371/journal.pone.0237106
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficient mice are better for modeling the transfusion of human blood components than wild-type mice

Abstract: Animal models are vital to the study of transfusion and development of new blood products. Post-transfusion recovery of human blood components can be studied in mice, however, there is a need to identify strains that can best tolerate xenogeneic transfusions, as well as to optimize such protocols. Specifically, the importance of using immunodeficient mice, such as NOD.Cg- Prkdc scid Il2rg tm1Wjl /SzJ (NSG) mice, to study human transfusion ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…The authors have previously observed that some engrafted mice may harbor only a single lineage of lymphocytes or monocytic cells; thus, longevity of these cells makes their detection alone insufficient evidence for HSC engraftment [34]. Although erythrocytes have a long life span, their survival in the circulation of NSG mice is short [33,39]. Thus, the authors' observation of fewer of these cells in the spleen than the bone marrow was not surprising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have previously observed that some engrafted mice may harbor only a single lineage of lymphocytes or monocytic cells; thus, longevity of these cells makes their detection alone insufficient evidence for HSC engraftment [34]. Although erythrocytes have a long life span, their survival in the circulation of NSG mice is short [33,39]. Thus, the authors' observation of fewer of these cells in the spleen than the bone marrow was not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments adhered to the principles of the current version of the National Research Council's Guide for the Care and Use of Laboratory Animals. Husbandry conditions have been previously detailed [33]. Euthanasia was performed according to the recommendations of the American Veterinary Medical Association.…”
Section: Xenografting Of Micementioning
confidence: 99%
“…Investigators adhered to the Animal Welfare Act Regulations and other Federal statues relating to the animals, and experiments involving animals, and the principles set forth in the current version of the Guide for Care and Use of Laboratory Animals, National Research Council. Mice were maintained under specific-pathogen free conditions as previously detailed [ 35 ] and euthanized according to the recommendations of the American Veterinary Medical Association. The standard diet was exchanged for irradiated Global 2018 rodent diet with 4100 ppm Uniprim (Envigo) ≥3 days before irradiation and the mice were maintained on this diet for a month.…”
Section: Methodsmentioning
confidence: 99%
“…Human platelets injected into WT mice circulate less than 2h, in contrast to mouse platelets transfused into mice that can circulate for several days. 87,88 We thus used mouse PEVs in our transfusion experiments, and yet most were undetectable from the blood circulation after 15min, pointing to their rapid uptake in surrounding tissues. In blood, the main absolute cellular target was the platelets, mostly because platelets outnumber leukocytes, which might suggest that PEVs might recycle molecules back to platelets.…”
Section: Discussionmentioning
confidence: 99%